Early Mover Advantages - Govert E. Bijwaard; Maarten C.W. Janssen; Emiel Maasland (Tinbergen Institute, 2005)
This paper analyzes empirically whether and if so to what extent later entrants in the European mobile telephony industry have a disadvantage vis-à-vis incumbents and early mover entrants. To analyze this question a dynamic model of market share development and a series of static models are considered. There is clear evidence of early mover advantage, mainly caused by the influence of the penetration rate: it pays to enter when still few people have acquired a mobile telephone. Another important determining factor is the Herfindahl–Hirschman Index at the moment of entry: it is significantly easier to enter a highly concentrated industry. Finally, there are important differences between countries, possibly indicating the relative strength of the national regulators.
Keywords: L51; L96; 330; Telecommunications; Entry; First-Mover Advantage; Mobilkommunikation; Markteintritt; Europa; Wettbewerbsvorteil